Pastor-Led Technology-Delivered Mental Health Promotion Program for Improving Quality of Life Among Older Black Adults in the United States - Carolyn M. Tucker; Kirsten G. Klein; Kaylyn A. Garcia; Eloise M. Harrison; Kelly L. Folsom; Guillermo M. Wippold (Journal of Prevention and Health Promotion, 2026)
Older Black adults experience high rates of adverse health concerns that contribute to high morbidity and premature mortality. To address these health disparities, it is recommended that health promotion interventions are culturally tailored (e.g., leveraging faith and spirituality) to the unique needs of older Black adults. Such interventions must recognize that older Black adults often report experiencing barriers to engagement in interventions such as transportation and cost. The purpose of the present study was to test a virtual Mental Health Promotion Program for Older Black Adults (MHPP-OBA) designed to improve health-related quality of life and decrease loneliness among older Black participants. The MHPP-OBA was designed to be delivered via Zoom by Black pastors and church leaders trained to be Mental Health Promotion Support Coaches. Training includes participation in a researcher-developed Mental Health Promotion Support Coach Skills (MHPSCS) Training Program. Trained mental health support coaches ( N = 28) implemented the MHPP-OBA among their respective older Black adult church members ( N = 192). Results demonstrated significant improvements in psychological, physical, and social health-related quality of life and significant decreases in loneliness from pre- to 2-week post-intervention that were maintained at 6-week post-intervention. The MHPSCS Training Program is an innovative program for training pastors and church leaders as mental health coaches. The MHPP-OBA is an accessible and sustainable mental health promotion intervention that serves as a model for promoting health-related quality of life among older Black adults.